사례분석을 통한 베이즈 정리 기반 TBM 터널 붕괴 리스크 우선순위 도출 연구 - 권기범; 강민규; 황병현; 최항석; Kwon, Kibeom; Kang, Minkyu; Hwang, Byeonghyun; Choi, Hangseok (KSCE Journal of Civil and Environmental Engineering Research, 2023)
Risk management is essential for preventing accidents arising from uncertainties in TBM tunnel projects, especially concerning managing the risk of TBM tunnel collapse, which can cause extensive damage from the tunnel face to the ground surface. In addition, prioritizing risks is necessary to allocate resources efficiently within time and cost constraints. Therefore, this study aimed to establish a TBM risk database through case studies of TBM accidents and determine a risk priority for TBM tunnel collapse using the Bayes theorem. The database consisted of 87 cases, dealing with three accidents and five geological sources. Applying the Bayes theorem to the database, it was found that fault zones and weak ground significantly increased the probability of tunnel collapse, while the other sources showed low correlations with collapse. Therefore, the risk priority for TBM tunnel collapse, considering geological sources, is as follows: 1) Fault zone, 2) Weak ground, 3) Mixed ground, 4) High in-situ stress, and 5) Expansive ground. In practice, the derived risk priority can serve as a valuable reference for risk management, enhancing the safety and efficiency of TBM construction. It provides guidance for developing appropriate countermeasure plans and allocating resources effectively to mitigate the risk of TBM tunnel collapse. TBM 터널 프로젝트 내 불확실성으로 인한 사고를 예방하기 위해 리스크 관리는 필수적이다. 특히, 터널 막장면부터 지표면까지의 광범위한 피해를 초래할 수 있는 TBM 터널 붕괴는 더욱 신중히 관리되어야 한다. 또한, 각 TBM 터널 프로젝트의 시간과 비용의 제약으로 인해, 합리적 수준의 대응조치 계획을 수립하기 위한 리스크 우선순위를 도출할 필요가 있다. 이에 따라, 본 연구는 TBM 사고 사례조사를 통해 TBM 리스크 데이터베이스를 구축하였고, 베이즈 정리를 활용하여 지질요인의 TBM 터널 붕괴 리스크 우선순위를 도출하였다. 총 87건의 TBM 사고사례를 기반으로 3가지 사건과 5가지 지질요인을 포함한 TBM 리스크 데이터베이스가 구축되었다. 이때, 자갈층 지반, 고수압 함수대는 관련 사례 수가 적어 통계적 편향을 방지하기 위해 제외되었다. 데이터베이스에 베이즈 정리를 적용한 결과, 단층대와 연약지반은 TBM 터널 붕괴의 발생확률을 상당히 증가시키나, 그 외 3가지 지질요인(복합지반, 높은 상재압력, 팽창성 지반)은 붕괴와 낮은 상관성을 보였다. 결과적으로, 지질요인의 TBM 터널 붕괴 리스크 우선순위는 다음과 같다: 1) 단층대, 2) 연약지반, 3) 복합지반, 4) 높은 상재압력, 5) 팽창성 지반.